Combination of quercetin and ivermectin: In vitro and in vivo effects against Haemonchus contortus - Borges, Dyego Gonçalves Lino (2020)
The aim of the present study was to evaluate the in vitro effect of quercetin combined with ivermectin (IVM) on Haemonchus contortus larvae and adults with different resistance profiles and demonstrate the in vivo anthelmintic action of this combination when used in sheep naturally infected. The effect of combination was evaluated based on the analysis of the mean effective concentration (EC50) obtained for larvae using the larval migration inhibition test and for adults using the motility test on females. The tests with larvae and adults were conducted using isolates with different degrees of susceptibility to IVM (sensitive, intermediate and highly resistant). The in vivo effect was evaluated based on the reduction in the egg count (FEC) and reduction in the count of adult helminths recovered after parasitological necropsy. Using the combination of quercetin with IVM, it was observed that in larvae, quercetin did not significantly reduce the EC50 for IVM in the sensitive and highly resistant isolates, but led to a significant reduction in the EC50 for IVM in the intermediate isolate. In adults, quercetin did not significantly reduce the EC50 for IVM in any of the isolates. No significant effect of the combination was found regarding the reduction in FEC or total count of parasites. The results of the in vitro and in vivo tests performed in the present study on quercetin activity underscore the importance of evaluating resistance-reversing agents among different stages of parasite development as well as among isolates with different resistance profiles. The action of quercetin combined with IVM on the motility of H. contortus larvae and adults was influenced by the degree of resistance and development stage of the parasite. The combination was effective only on intermediate resistant larvae. No action of the combination against adults was found. Moreover, this combination, when administered through the intra-abomasal route, was not effective at reducing the FEC and parasite load of naturally infected sheep.